Hospital admission and vaccination as predictive factors of long COVID-19 symptoms - Romero-Rodríguez, Esperanza; Pérula-de Torres, Luis Ángel; Castro-Jiménez, Rafael; González-Lama, Jesús; Jiménez-García, Celia; González-Bernal, Jerónimo J.; González-Santos, Josefa; Vélez-Santamaría, Rodrigo; Sánchez-González, Esteban; Santamaría-Peláez, Mirian (Frontiers in Medicine, 2022)
Background: Since the beginning of the COVID-19 pandemic, a great viability has been identified in the symptomatology that occurs in SARS-Cov-2 infection that affects all organs and body systems; this symptomatology, sometimes, can be maintained over time giving rise to the so-called Long Covid or Post Covid. It is important to delve into the clinical characterization of these patients, as well as to take into account the influence of factors such as hospitalization, admission to ICU, pneumonia or vaccination status on the persistence of symptoms. This is the aim of this study. Material and methods: Observational, descriptive, multicenter and retrospective study was designed with a series of cases of people who presented Long COVID, which includes univariate, bivariate and multivariate analysis. Data was obtained from an on-line ad hoc questionnaire and statistical analysis was performed with SPSS software 25th version program (IBM-Inc., Chicago, IL, USA). Results: Odds Ratio analysis and logistic regression models offer predictive factors (positive or negative) for symptoms headache, menstrual disorders, joint pain, cough, chills, nasal congestion, back pain, abdominal pain, weight loss, eye discomfort, facial erythema, itching, tremors, dizziness, seizures, sleeping difficulty, dry eyes, palpitations, fatigue, paresthesias, dyspnoea, aphonia, chest pain and high blood pressure, vomiting, memory loss, brain fog, hypothermia, low blood pressure, sputum or phlegm, lack of concentration, hair loss and erectile dysfunction. For the rest of the symptoms, hospitalization, ICU admission, pneumonia and vaccination are not predictors. Conclusions: This research provides evidence on the clinical characterization of patients suffering from Long COVID in order to offer them the most appropriate treatments.